Incidence of Basal Cell Carcinoma and Squamous Cell Carcinoma in Patients on Antiprogrammed Cell Death-1 Therapy for Metastatic Melanoma. Issue 7 (September 2018) - Zhao, Cathy Yunjia; Hwang, Shelley Ji Eun; Anforth, Rachael; Carlos, Giuliana; Chou, Shaun; Carlino, Matteo; Fernández-Peñas, Pablo
Abstract : Systemic melanoma therapies have the potential to affect basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cuSCC) development. In this study, we aim to compare the incidence of BCC and cuSCC in patients with metastatic melanoma treated with antiprogrammed cell death-1 (anti-PD1), BRAF inhibitor (BRAFi) monotherapy or dabrafenib and trametinib combination therapy (CombiDT) with a group of control patients having similar risk factors. We reviewed the records of melanoma patients on anti-PD1, BRAFi, or CombiDT, and patients from the High-Risk Melanoma Clinic, Westmead Hospital. We also performed an immunohistochemical analysis of BCCs under anti-PD1 compared with controls using PD1, PD-L1, CD3, CD8, and CD20 stains. For the results, in all, 340 patients were included; 82 on anti-PD1, 134 on BRAFi, 69 on CombiDT, and 55 controls. BRAFi had the highest incidence of BCC (12.7%), followed by CombiDT (10.1%) and anti-PD1 (2.4%). The incidence of BCC was significantly lower in patients on anti-PD1 (2.4% vs. 19.4%; P <0.001) compared with controls. Patients on anti-PD1 were 8.54 times less likely to develop BCC than the controls [hazard ratio, 0.117 (95% confidence interval, 0.026–0.526), P =0.005]. BRAFi and CombiDT showed no significant differences in BCC incidence compared with controls. BRAFi had the highest cuSCC incidence (23.9%), followed by anti-PD1 (7.3%) and CombiDT (2.9%). The incidence of cuSCC was significantly higher in patients on BRAFi (23.9% vs. 3.5%; P <0.001) compared with controls, but anti-PD1 and CombiDT showed no differences in cuSCC incidence compared with controls. Immunohistochemistry analysis of 10 BCC from under anti-PD1 and 8 BCC from controls patients showed that while all BCC had negative PD-L1 staining, the percentage of PD1 staining in anti-PD1 group is significantly lower than that of the control group (independent t test, 8% vs. 26%; P <0.001). In conclusion, our study suggests that anti-PD1 therapy decreases the incidence of BCC, as a result of the PD1/PD-L1 blockade. Future studies investigating the role of anti-PD1 in suppressing or treating BCC may be warranted.